Whole Exome Sequencing Analysis in Fetal Skeletal Dysplasia Detected by Ultrasonography: An Analysis of 38 Cases - Peng, Ying; Yang, Shuting; Huang, Xiaoliang; Pang, Jialun; Liu, Jing; Hu, Jiancheng; Shen, Xinzhao; Tang, Chengyuan; Wang, Hua (Frontiers in Genetics, 2021)
Background: Skeletal dysplasias (SDs) are a heterogeneous group of genetic disorders that primarily affect bone and cartilage. This study aims to identify the genetic causes for fetal SDs, and evaluates the diagnostic yield of prenatal whole-exome sequencing (WES) for this disorder. Methods: WES was performed on 38 fetuses with sonographically identified SDs and normal results of karyotype and single nucleotide polymorphism (SNP) analysis. Candidate variants were selected by bioinformatics analysis, and verified by Sanger sequencing. Results: WES revealed pathogenic or likely pathogenic variants associated with SDs in 65.79% (25/38) of fetuses, variants of uncertain significance in SDs-related genes in 7.89% (3/38) cases, and incidental findings in 31.58% (12/38) fetuses. The SDs-associated variants identified in the present study affected 10 genes, and 35.71 % (10/28) of the variants were novel. Conclusion: WES has a high diagnostic rate for prenatal SDs, which improves pregnancy management, prenatal counselling and recurrence risk assessment for future pregnancies. The newly identified variants expanded mutation spectrum of this disorder.